Volitional Qualities as a Means of Physical Education of a Personality - Yuldashevich, Turdimurodov Dilmurod (European Journal of Life Safety and Stability (2660-9630), 2023)
The article reveals the possibilities of developing volitional qualities in the physical development of a person, shows the importance of self-control and self-regulation in competitive activity, both for beginners and highly skilled athletes. The structure of volitional qualities is singled out, recommendations for the development of volitional qualities in the process of physical education are given, the basic principles of self-education of volitional qualities are given.